An innovative and meaningful scaffolded curriculum approach to Environmental Health education in Western Australia - Oosthuizen, Jacques; Masaka, Edmore; Doherty, Sally-Anne; Staples, Kerry; Dine, Gary; Vance, Gerard; Wallace, Ruth (Frontiers in Education, 2024)
There has been a critical shortage of qualified Environmental Health Officers (EHOs) both globally and in Australia that has plagued the profession for decades. At Edith Cowan University (ECU), Perth, Western Australia, an undergraduate degree in Environmental Health (EH) was developed in 2006, however, viability was problematic, and the course was under threat of closure. In 2016 both the EH and occupational safety and health (OSH) majors were due for re-accreditation and since there was significant overlap between the two courses both majors were revised and combined into one (Occupational and Environmental Health and Safety). This new qualification has subsequently been accredited by Environmental Health Australia (EHA), as well as the Australian OHS Education Accreditation Board (AOHSEAB) and the British Institution of Occupational Safety and Health (IOSH). The new dual accredited course has had excellent graduate outcomes and provides graduates with the flexibility to move between traditional OHS and EH roles. In some smaller local governments, and in industry, ECU graduates have been employed to work in both roles.. The curriculum was developed in consultation with industry and has an embedded year-long diploma course that consists of eight units (subjects/courses) that prepare graduates to work in a support role to EHOs. The Diploma of Environmental Health course is a scaffolded course that is embedded in the degree, and it has been recognized by the State Government as a qualification leading to appointment as authorised officers under the Public Health Act 2016 (WA). The diploma is more than a pathway course as it is a stand-alone qualification that leads to gainful employment. Most students now enroll in the diploma, initially and gain employment as a Technical Officer, and then progress on to complete the EH degree on a part-time basis while employed in the profession. The diploma is also an exit option for students who struggle with the academic requirements of some of the more traditionally difficult units such as physics, chemistry, and statistics and the EH degree is now a viable university course with excellent graduate employment outcomes.